Midazolam but not propofol for sedation impairs long term spatial memory in mice (Annals of Medical Research, 2022)
Aim: Sedation may alter memory and learning. This study is designed to investigate the effects of short-acting sedative agents, propofol and midazolam, on learning and memory in mice.Materials and Methods: Thirty male, adult Swiss-albino mice were randomly assigned into three groups as control, midazolam and propofol groups (n=10, for each). Experiments on learning and memory were started 72 hours after the intraperitoneal injections. Learning and short term memory development in mice were evaluated by Morris Water Maze conducted for five consecutive days, and on the 19th day long term memory formation was evaluated by the same experimental set up. Time for the mice to find the escape platform (latency), total distance covered and swimming speed were recorded and evaluated statistically.Results: Propofol and midazolam administrations were found to increase the latency. In addition, midazolam was found to impair memory development, when compared to other two groups (p < 0,01). Swimming speed and distance covered as indicators of the motor activity decreased gradually from the beginning, however there was no statistically difference between the groups (p > 0.05).Conclusion: Use of midazolam and propofol prolonged the latency on the first three days. Midazolam was also found to affect the memory development negatively.